Photography As A Bridge To Intercultural Interaction In Bali During The Netherland Indies Colonial Period Of The 1920-1930S - Bayu Pramana, I Made (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2019)
This article presents the process of commencing inter-cultural interactions and artistic collaboration between Balinese and western photographers through photography. In the beginning, the photography project only showed visual record of the Kings, the royal family along with the royal government apparatus in Bali. Beginning with Gregor Krause, a colonial doctor who practiced photography, the others photographers then began exploring nature, culture, art and Balinese society into recording their photographic works. The activity then continued to be an artistic collaboration between westerners as photographers and Balinese as photo models. Not only that, the collaboration also extends to the incorporation of many western cultural elements into photography properties. In addition, the models that appear in photographic works are not only from the royal community, but begin to spread to ordinary residents, artists and their environment. Through the bridge of photography, many western artists combine their ideas with Balinese artists to design and create works of art in the needs of photographic documentation. The collaborative work then attracted tourists to Bali to enjoy the exotica of Bali which was first collaborated by western photographers and writers.